Применение генетического алгоритма в задачах допускового синтеза микрополосковых устройств - Krischuk, V. N.; Karpukov, L. M.; Shilo, G. N.; Farafonov, A. Yu.; Artyushenko, B. A. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A procedure for assigning tolerances in microstrip devices with the aid of a genetic algorithm is proposed. The use of a genetic algorithm enables the solution of problems with non-monotonic objective functions and non-standard constraints. The tolerance analysis model is based on evaluating the membership of search beam vertices within the tolerance region.